Gender differences in bicycle saddle pressure distribution during seated cycling - Potter, J. J.; Sauer, J. L.; Weisshaar, C. L.; Thelen, D. G.; Ploeg, H. L. (Medicine & Science in Sports & Exercise, 2008)
Introduction: The purpose of this study was to investigate the influence of gender, power, hand position, and ischial tuberosity (IT) width on saddle pressure during seated stationary cycling.